Evaluasi Manajemen Pembinaan Olahraga Sepakbola di Sekolah Sepak Bola Bank Sulselbar FC Makassar - Ahmad Latando Paturusi; Hasyim Hasyim; Benny Badaru; Suriah Hanafi; Muh. Adnan Hudain (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2026)
This study is a descriptive study that aims to explain and describe the management of sports coaching at the Bank Sulselbar FC Makassar soccer school. The variables in this study are planning, organizing, implementing, and supervising. The population in this study is the entire SSB Bank Sulselbar FC, while the sample consists of 3 managers, 3 coaches, 20 players, and 4 parents. The research data was obtained with the validity and reliability of the questionnaire first tested for validity and approved by two experts. The instruments used in this study were questionnaires and interviews. The data analysis technique used descriptive statistical analysis with the help of the SPSS 27 program. Based on the results of the data analysis, it can be concluded that planning management is in the good category with a percentage of 73.33%, while organizing, implementing, and supervising management are each in the good category with a percentage of 66.67%. These findings indicate that coaching management has been carried out effectively, although continuous improvement efforts are still needed to optimize every aspect of management.